The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11999-011-2009-5
|View full text |Cite
|
Sign up to set email alerts
|

Precontoured Superior Locked Plating of Distal Clavicle Fractures: A New Strategy

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 29 publications
5
64
0
5
Order By: Relevance
“…With the advent of the locking plate, several site-specific locking plates, including a distal clavicle locking plate, are now available to provide improved fixation with few complications and the advantage of a lower rate of subsequent surgery for hardware removal [14]. Studies have reported excellent results of distal clavicle fractures treated with locking plate [14,15,17,26,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advent of the locking plate, several site-specific locking plates, including a distal clavicle locking plate, are now available to provide improved fixation with few complications and the advantage of a lower rate of subsequent surgery for hardware removal [14]. Studies have reported excellent results of distal clavicle fractures treated with locking plate [14,15,17,26,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported excellent results of distal clavicle fractures treated with locking plate [14,15,17,26,29,30]. Treatment for unstable distal clavicle fractures using a locking T-plate and a CC PDS (polydioxansulfate) cerclage can provide good and reliable clinical results and a 100 % union rate [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] described the advantageous role of hook plate fixation in their comparative study between hook plate and tension band. Andersen et al [27] reported 94% union rate with precountered superior locking plate fixation for displaced distal clavicle fractures. Peri-implant fracture has been reported in one case and infected nonunion in the other in their study.…”
Section: Discussionmentioning
confidence: 99%
“…To counter this one of the studies added a suture anchor or a simple non absorbable suture for coracoclavicular fixation. 15 In few cases they used a screw through the plate and fixed it to the coracoid. Loss of fixation in the distal fragment leading to implant failure, entry of screw into the AC joint and infection due to an extensive dissection are some of the possible complications.…”
Section: Discussionmentioning
confidence: 99%